Respiratory disease and cardiovascular morbidity. Issue 9 (18th August 2005) - Koskela, R-S; Mutanen, P; Sorsa, J-A; Klockars, M
Abstract : Background: Work related dust exposure is a risk factor for acute and chronic respiratory irritation and inflammation. Exposure to dust and cigarette smoke predisposes to exogenous viral and bacterial infections of the respiratory tract. Respiratory infection can also act as a risk factor in the development of atherosclerotic and coronary artery disease. Aims: To investigate the association of dust exposure and respiratory diseases with ischaemic heart disease (IHD) and other cardiovascular diseases (CVDs). Methods: The study comprised 6022 dust exposed (granite, foundry, cotton mill, iron foundry, metal product, and electrical) workers hired in 1940–76 and followed until the end of 1992. National mortality and morbidity registers and questionnaires were used. The statistical methods were person-year analysis and Cox regression. Results: Co-morbidity from cardiovascular and respiratory diseases ranged from 17% to 35%. In at least 60% of the co-morbidity cases a respiratory disease preceded a cardiovascular disease. Chronic bronchitis, pneumonia, and upper respiratory track infections predicted IHD in granite workers (rate ratio (RR) = 1.9; 95% CI 1.38 to 2.72), foundry workers (2.1; 1.48 to 2.93), and iron foundry workers (1.7; 1.16 to 2.35). Dust exposure was not a significant predictor of IHD or other CVD in any group. Dust exposure was related to respiratory morbidity. Thus, some respiratory diseases appeared to act as intermediate variables in the association of dust exposure with IHD. Conclusion: Dust exposure had only a small direct effect on IHD and other CVD. IHD morbidity was associated with preceding respiratory morbidity. A chronic infectious respiratory tract disease appeared to play an independent role in the development of IHD.